Application of Stad Type Learning Models to Improve Activity and Student Learning Outcomes - Desnita Desnita; Rr Sri Kartikowati; Makhdalena Makhdalena (Universitas Riau, 2021)
This research is motivated by the low activity and student learning outcomes in learning. One alternative that is used to overcome the low activity and learning outcomes of social studies subjects is by using the Student Team Achievement Division (STAD) type of cooperative learning model with LKPD assistance. The purpose of this study was to analyze student learning activities and outcomes using the STAD type cooperative learning model assisted by Student Workshet (LKPD). This research was an experimental study using the Pre-Test Post-Test Control Group Design. The data used consists of primary and secondary data. The data were collected using test results of learning and observation sheets to determine student learning activities. The total population was 348 people with a sample size of 78 people with a purposive sampling technique. The method of analysis used the independent sample t-test. The results showed that the student's learning activity was declared active with a high category as long as the cooperative learning model type STAD was assisted by LKPD and the learning outcomes obtained a significance value of 0.000 with a significance level of 0.05. It can be concluded that there is an increase in student activity and learning outcomes using the STAD type cooperative learning model assisted by LKPD.